European primary forest database v2.0 - Sabatini, Francesco Maria; Bluhm, Hendrik; Kun, Zoltan; Aksenov, Dmitry; Atauri, José A; Buchwald, Erik; Burrascano, Sabina; Cateau, Eugénie; Diku, Abdulla; Duarte, Inês Marques; Fernández López, Ángel B; Garbarino, Matteo; et al. (Scientific data, 2021)
Primary forests, defined here as forests where the signs of human impacts, if any, are strongly blurred due to decades without forest management, are scarce in Europe and continue to disappear. Despite these losses, we know little about where these forests occur. Here, we present a comprehensive geodatabase and map of Europe's known primary forests. Our geodatabase harmonizes 48 different, mostly field-based datasets of primary forests, and contains 18,411 individual patches (41.1 Mha) spread across 33 countries. When available, we provide information on each patch (name, location, naturalness, extent and dominant tree species) and the surrounding landscape (biogeographical regions, protection status, potential natural vegetation, current forest extent). Using Landsat satellite-image time series (1985-2018) we checked each patch for possible disturbance events since primary forests were identified, resulting in 94% of patches free of significant disturbances in the last 30 years. Although knowledge gaps remain, ours is the most comprehensive dataset on primary forests in Europe, and will be useful for ecological studies, and conservation planning to safeguard these unique forests.
Keywords: lesy; Databases, Factual; databáze faktografické; zachování přírodních zdrojů; Europe; Forests; Conservation of Natural Resources; Evropa